Nonprompt direct-photon production in Au+Au collisions at sNN =200 GeV - Abdulameer, N.J.; Oskarsson, A.; Silvermyr, D. ; 0000-0002-0526-5791; Zou, L. (Physical Review C, 2024)
The measurement of the direct-photon spectrum from Au+Au collisions at sNN=200 GeV is presented by the PHENIX Collaboration using the external-photon-conversion technique for 0%-93% central collisions in a transverse-momentum (pT) range of 0.8-10 GeV/c. An excess of direct photons, above prompt-photon production from hard-scattering processes, is observed for pT